Balancing Economic Growth and Social Equity: A Legal and Conceptual Analysis of Indonesian Agrarian Reform in the Agribusiness Sector - Dina Mukti Yatulloh; Shalsabila Putri Fairuz Zahra; Cikal Gumiwang Nagari (Arkus, 2025)
Indonesia faces the persistent challenge of balancing economic growth with social equity in its agribusiness sector. This study analyzes how legal and conceptual aspects of agrarian reform policies contribute to this balancing act, particularly in the context of rising agribusiness investment and the persistence of smallholder farming. A normative juridical method was employed, incorporating statute, historical, and conceptual approaches. Legal documents, historical records, and academic literature were analyzed. Simulation data, based on government statistics and existing research, was used to model the potential impact of different policy scenarios on economic growth and social equity. Indonesia's legal framework, while promoting land redistribution and tenure security, exhibits inconsistencies that can favor large-scale agribusiness interests. This can lead to unequal access to land and resources, potentially hindering inclusive growth. Simulation data suggests that strengthening land tenure security, improving access to finance, and promoting sustainable agricultural practices can contribute to both economic growth and social equity. In conclusion, optimizing agrarian reform requires a more nuanced approach that prioritizes social equity alongside economic growth. This includes strengthening land rights for smallholder farmers, improving access to resources, and promoting sustainable agricultural practices.